Ethylene-propylene rubber material with self-repairing function and preparation method thereof
Patent Information
- Application Number
- CN202610949065.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-06-29
AI Technical Summary
[0002]在核电及高能辐射环境中,电缆及密封材料长期暴露于γ射线或中子辐照下,材料分子链易发生断裂、氧化降解及交联结构破坏,导致力学性能显著衰退,制约使用寿命与安全性
(1)本申请的复合乙丙橡胶材料体系能够在核辐射环境下实现裂纹的快速、原位自修复,显著改善了传统材料在高剂量辐照下力学性能衰退的问题。通过TiO2在UiO-66多孔结构中均匀生成,并与Cu形成协同电子转移体系,材料在辐照过程中持续生成高浓度自由基,优先在裂纹区域富集并触发分子链断裂-重构反应,实现微观裂纹的闭合与宏观性能恢复。
Abstract
Description
Technical Field
[0001] This invention relates to the field of ethylene propylene rubber materials technology, and in particular to an ethylene propylene rubber material with self-healing function and its preparation method. Background Technology
[0002] In nuclear power and high-energy radiation environments, cables and sealing materials are exposed to gamma rays or neutron irradiation for a long time. The molecular chains of the materials are prone to breakage, oxidative degradation and destruction of cross-linked structures, resulting in a significant decline in mechanical properties and limiting service life and safety.
[0003] Traditional radiation-resistant modification methods mainly rely on adding fillers or stabilizers. These methods can only delay the aging process and cannot repair existing microcracks and structural defects. Existing self-healing strategies mostly rely on external stimuli such as light or heat, or on releasing repair agents through microcapsules to achieve crack repair. However, in a nuclear radiation environment, these methods often fail to achieve timely, in-situ repair due to unstable external conditions, difficulty in penetrating deeply, or the asynchronous nature of repair triggering and damage.
[0004] At the same time, existing materials have limited free radical generation under irradiation conditions, random distribution, and short lifetime, resulting in insufficient spontaneous repair capabilities and an inability to effectively restore microscopic and macroscopic mechanical properties.
[0005] Therefore, there is an urgent need to develop a material system that can achieve efficient, uniform, and real-time repair in a radiation environment to improve the reliability and service life of materials under nuclear energy and high-energy radiation conditions.
[0006] Therefore, this invention is proposed. Summary of the Invention
[0007] To address the aforementioned technical problems, this application provides an ethylene propylene rubber material with self-healing function, which can achieve rapid, in-situ self-healing of cracks under nuclear radiation environment, thereby significantly improving the mechanical properties and service life of the material.
[0008] In order to achieve the objective of this invention, the following technical solution is adopted: This application provides a self-healing composite material, namely TiO2@UiO-66 / Cu. In the TiO2@UiO-66 / Cu composite material, TiO2 is formed by in-situ hydrolysis of tetrabutyl titanate and dispersed in the porous structure of the UiO-66 metal-organic framework. Cu is distributed as Cu... 2+ The form is loaded in the UiO-66.
[0009] This application also provides a self-healing ethylene propylene rubber material. Using the above-mentioned self-healing composite material, the ethylene propylene rubber material includes a ternary ethylene propylene rubber matrix, TiO2@UiO-66 / Cu dispersed in the ternary ethylene propylene rubber matrix, and benzophenone.
[0010] Furthermore, based on 100 phr EPDM rubber, the amount of TiO2@UiO-66 / Cu added is 1-5 phr, and the content of benzophenone is 3-8 phr.
[0011] Furthermore, in the EPDM rubber matrix, based on 100 phr EPDM rubber, the EPDM rubber matrix includes 40-45 phr rubber carbon black, 10-20 phr paraffin oil, 5-10 phr zinc oxide, 1-3 phr stearic acid, and 1-2 phr dicumyl peroxide.
[0012] This application also provides a method for preparing the above-mentioned ethylene propylene rubber material with self-healing function, including the following steps: Tetrabutyl titanate was dissolved in anhydrous ethanol and added dropwise to a dispersion of UiO-66. It was hydrolyzed to form TiO2@UiO-66. After treatment with Cu(NO3)2 solution, TiO2@UiO-66 / Cu was obtained. The EPDM rubber matrix, TiO2@UiO-66 / Cu and benzophenone are mixed, compounded and vulcanized.
[0013] Furthermore, the reaction to form TiO2@UiO-66 by hydrolysis is initiated by adding 1-5 vol% aqueous ethanol as a trigger, followed by calcination at 450-550°C for 2-4 hours.
[0014] Furthermore, the concentration of the Cu(NO3)2 solution is 0.01-0.1M, and the treatment time is 6-12h.
[0015] Furthermore, the solid-liquid ratio of the TiO2@UiO-66 to the Cu(NO3)2 solution is 1g:50mL.
[0016] Furthermore, the mixing is carried out at 60-80℃, the vulcanization temperature is 165-175℃, the vulcanization pressure is 8-12MPa, and the vulcanization time is 10-20min.
[0017] This invention also provides the application of the aforementioned self-healing ethylene propylene rubber material as a cable insulation or sealing material in a nuclear radiation environment.
[0018] The present invention has the following technical effects: (1) The composite ethylene propylene rubber material system of this application can achieve rapid and in-situ self-repair of cracks under nuclear radiation environment, which significantly improves the problem of mechanical property degradation of traditional materials under high dose irradiation. Through the uniform generation of TiO2 in the UiO-66 porous structure and the formation of a synergistic electron transfer system with Cu, the material continuously generates high concentration of free radicals during irradiation, which preferentially accumulate in the crack area and trigger molecular chain breakage-reconstruction reaction, thereby achieving the closure of microcracks and the restoration of macroscopic properties. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] In the radiation environment of nuclear power systems, cable insulation materials are exposed to gamma rays or neutrons for a long time, which can easily cause irreversible structural damage. This damage is mainly manifested in molecular chain breakage, oxidative degradation, and cross-linking structure destruction, which leads to the deterioration of macroscopic mechanical properties and seriously restricts their service life and safety.
[0021] Traditional methods mainly enhance the radiation resistance of materials by adding fillers or stabilizers, but these methods can only delay damage and cannot repair existing defects. Long-term use will still result in localized aging and microcracks.
[0022] Currently, while some self-healing materials can repair damage through light or heat, these external conditions are often unstable in a nuclear radiation environment and are difficult to apply evenly to the material's interior, and may even fail to penetrate deeply. Microencapsulated repair agents are also used, releasing the repair filler through crack propagation and puncture; however, these methods are difficult to synchronize with the radiation-induced damage process, making timely, in-situ repair challenging in practical applications.
[0023] Therefore, this application proposes a radiation-responsive self-healing TiO2@UiO-66 / Cu / BP composite material based on an EPDM rubber system. The UiO-66 MOF porous structure is combined with tetrabutyl titanate as Ti source, copper nitrate as Cu source, and benzophenone (BP) to form a multi-level synergistic free radical system, thereby realizing the degradation-dynamic reconstruction-performance recovery of the material at the crack under irradiation conditions.
[0024] In a first aspect, this application provides a self-healing composite material, wherein the composite material is TiO2@UiO-66 / Cu, and the TiO2 in TiO2@UiO-66 / Cu is formed by in-situ hydrolysis of tetrabutyl titanate and dispersed in the porous structure of the UiO-66 metal-organic framework, and Cu is in the form of Cu 2+ The form is loaded in the UiO-66.
[0025] In this application's self-healing composite material, the UiO-66 MOF structure was chosen primarily because of its high structural stability under gamma irradiation. Under irradiation, the porous structure of UiO-66 MOF prevents the overall framework from collapsing instantly. In contrast, many other MOFs (especially those based on transition metal-N coordination or weak coordination bonds) are prone to rapid decomposition or structural runaway under gamma irradiation, making it difficult to achieve a controlled process that simultaneously preserves structure and transforms function. Therefore, the core function of this UiO-66 MOF precursor is to provide a spatially uniform reaction vessel, allowing for the uniform generation of TiO2 within it and ensuring a reasonable spatial distribution of Ti and Cu, thereby better leveraging their synergistic effect.
[0026] Tetrabutyl titanate serves as the Ti source. When dissolved in anhydrous ethanol and uniformly mixed with other components in the system, it undergoes a gradual transformation, reacting with water to transform into intermediate Ti species. These intermediate Ti species refer to the Ti-OH formed after the hydrolysis of tetrabutyl titanate and the Ti-O-Ti clusters formed by further condensation. These structures have not yet fully transformed into crystalline TiO2, but they are in the process of gradually building the TiO2 framework. These small molecules gradually link together, eventually forming large-area TiO2 particles within the material.
[0027] In other words, TiO2 is not added at the beginning, but grows gradually within the system. This results in a more uniform distribution of TiO2, a tighter bond with the Cu and MOF structures, and a shorter reaction distance, thereby improving the self-healing effect.
[0028] Compared to directly introducing TiO2 powder, its particles are prone to agglomeration and difficult to disperse uniformly, unlike Cu. 2+ The weak interfacial bonding in the MOF structure can lead to uneven reactions and reduced electron utilization efficiency. Therefore, TBOT has significant advantages.
[0029] During irradiation, TiO2 absorbs high-energy gamma rays and generates electron-hole pairs through ionization and secondary electron processes. The electrons in these pairs have reducing properties and can react with oxygen to generate superoxide radicals (·O2). - Holes, on the other hand, have strong oxidizing properties and can react with OH-. -Alternatively, H2O may react to generate hydroxyl radicals, which prepare for subsequent self-repair. The energy of gamma rays in a nuclear power environment is much higher than the band gap of TiO2, which can continuously excite the above ionization process. Some of the high-energy electrons generated transfer energy to benzophenone, causing it to change from the ground state to the excited state; the other part is due to the rapid recombination and disappearance of electron-hole pairs in traditional TiO2, thus reducing the electron energy utilization rate.
[0030] To address this issue, this application introduces Cu doping to create defect energy levels in TiO2 crystals and constructs Cu... 2+ / Cu + Reversible system. Cu 2+ / Cu + The cycle enables reversible capture and transfer of electrons, thus acting as an effective electron transfer station, through Cu 2+ / Cu + The reversible cycle not only improves electron utilization efficiency but also continuously generates reactive oxygen free radicals.
[0031] BP→BP*(1) BP*+EPDM→·BP+·R(2) Equations 1 and 2 show that BP, after entering the excited state, has a strong hydrogen extraction capability, which will abstract hydrogen atoms from the EPDM molecular chain to generate polymer radicals (R·). This process is not essentially destroying the molecular chain, but rather transforming the originally stable, non-reactive chain segments into active sites that can participate in the reaction.
[0032] These newly generated free radicals randomly combine with existing free radicals in the system (such as irradiated free radicals or oxidative free radicals). However, in this system, the reaction is not completely disordered. On the one hand, the crack region, due to its loose structure and high surface energy, is more likely to accumulate free radicals, resulting in a significantly higher concentration of free radicals in this region than inside the material. On the other hand, the chain ends generated by irradiation fracture are themselves in a high-energy unstable state, exhibiting stronger reactivity and being more likely to undergo preferential recombination reactions.
[0033] Therefore, although there is some random reaction among free radicals, under conditions where they are more likely to meet and react in the crack region, EPDM segments tend to crosslink or reconstruct with the fractured chain ends, thereby achieving effective crack repair rather than simply resulting in ineffective random consumption. Ultimately, this spatially biased free radical reaction causes the system to exhibit "prioritize repair where damage occurs," rather than overall disordered crosslinking.
[0034] In existing technologies, while pure EPDM does generate free radicals under gamma irradiation, these free radicals are randomly distributed, have low concentrations, short lifetimes, and are easily terminated by oxygen or other substances. Furthermore, due to restricted molecular chain movement, free radicals on both sides of the crack cannot effectively contact and recombine, thus hindering spontaneous repair.
[0035] In this system, the synergistic cycling of TiO2 and Cu continuously provides electrons and promotes the generation of active species, maintaining high reactivity in the crack region. The generation rate is significantly higher than the rate at which oxygen terminates the reaction, allowing oxygen to participate more in the chain reaction process rather than simply acting as a passivator. These free radicals further undergo rapid recombination reactions, forming new C-C or CO bonds, thus reconnecting the molecular chains and effectively closing the cracks. Furthermore, because TiO2 is uniformly distributed throughout the material, this self-healing mechanism extends beyond the surface into the interior of the material, achieving structural repair on a global scale.
[0036] Secondly, this application also provides an ethylene propylene rubber material with self-healing function. Using the above-mentioned composite material with self-healing function, the ethylene propylene rubber material includes a ternary ethylene propylene rubber matrix, TiO2@UiO-66 / Cu dispersed in the ternary ethylene propylene rubber matrix, and benzophenone.
[0037] In some embodiments, based on 100 phr EPDM rubber, the amount of TiO2@UiO-66 / Cu added is 1-5 phr, and the content of benzophenone is 3-8 phr.
[0038] In some embodiments, the EPDM rubber matrix, based on 100 phr EPDM rubber, comprises 40-45 phr rubber carbon black, 10-20 phr paraffin oil, 5-10 phr zinc oxide, 1-3 phr stearic acid, and 1-2 phr dicumyl peroxide.
[0039] This application also provides a method for preparing the above-mentioned ethylene propylene rubber material with self-healing function, including the following steps: Tetrabutyl titanate was dissolved in anhydrous ethanol and added dropwise to a dispersion of UiO-66. It was hydrolyzed to form TiO2@UiO-66. After treatment with Cu(NO3)2 solution, TiO2@UiO-66 / Cu was obtained. The EPDM rubber matrix, TiO2@UiO-66 / Cu and benzophenone are mixed, compounded and vulcanized.
[0040] In some embodiments, the hydrolysis to form TiO2@UiO-66 reaction is initiated by adding 1-5 vol% aqueous ethanol as a trigger, followed by calcination at 450-550°C for 2-4 hours.
[0041] In some embodiments, the concentration of the Cu(NO3)2 solution is 0.01-0.1M, and the treatment time is 6-12h.
[0042] In some embodiments, the solid-liquid ratio of the TiO2@UiO-66 to the Cu(NO3)2 solution is 1g:50mL.
[0043] In some embodiments, the mixing is carried out at 60-80°C, the vulcanization temperature is 165-175°C, the vulcanization pressure is 8-12 MPa, and the vulcanization time is 10-20 min.
[0044] This application also provides an application of the above-mentioned ethylene propylene rubber material with self-healing function as a cable insulation or sealing material in a nuclear radiation environment.
[0045] The following is a detailed explanation using specific embodiments: Example 1: 1) Preparation of EPDM matrix Ethylene propylene diene monomer (EPDM, ethylene content 50%-70%, Mooney viscosity 60±5 ML (1+4) 125℃) was selected as the matrix material. Then, carbon black N550 (40 phr) was added as a reinforcing filler, paraffin oil (10 phr) was added to improve processing fluidity, zinc oxide (5 phr) was added as an activator, and stearic acid (1 phr) was added as a dispersant. The mixture was then mixed for 10 min at 60℃ using a two-roll mill. Subsequently, dicumyl peroxide (DCP, 1.5 phr) was added and rapidly mixed at ≤50℃. The mixture was then allowed to stand at room temperature for 12 h to eliminate internal stress, thus obtaining the EPDM matrix.
[0046] 2) Preparation of UiO-66 MOF structure ZrCl4 (0.233 g, 1.0 mmol) was dissolved in 50 mL of anhydrous N,N-dimethylformamide (DMF) and sonicated for 15 min. Then terephthalic acid (H2BDC, 0.166 g, 1.0 mmol) was added and the mixture was magnetically stirred at room temperature for 60 min.
[0047] Add 3 mL of glacial acetic acid, transfer the solution to a 50 mL polytetrafluoroethylene-lined reactor, and solvothermal react at 135 °C for 18 h. After the reaction was completed, the product was naturally cooled to room temperature. The product was collected by centrifugation at 8000 rpm and washed three times with DMF to remove unreacted ligands. Then, it was soaked in anhydrous ethanol for 24 h (the ethanol was replaced every 8 h) to exchange solvents and improve the pore openness. Finally, it was vacuum dried at 90 °C for 12 h to obtain pure UiO-66 porous crystal material.
[0048] 3) Introducing UiO-66 MOF structure with Ti and Cu Tetrabutyl titanate (TBOT) was dissolved in anhydrous ethanol at a mass fraction of 20 wt% as the Ti source and stirred at room temperature. Subsequently, fully dried UiO-66 (based on 1g) was weighed and dispersed in 50mL of anhydrous ethanol, sonicated for 30min, and then the above TBOT / ethanol solution was slowly added dropwise to the UiO-66 dispersion system, and magnetic stirring was continued at room temperature for 12h.
[0049] 5 vol% aqueous ethanol was slowly introduced into the system to trigger a hydrolysis-condensation reaction, which caused TBOT to rapidly hydrolyze to generate Ti-OH intermediates and further rapidly condense to form a Ti-O-Ti network structure. Calcination at 550℃ for 2 h in air was carried out to allow the Ti-O-Ti network to fully crystallize and rearrange, achieving uniform dispersion of TiO2 nanocrystals at the original UiO-66 derived pore structure positions. The system was then left to stand at room temperature for another 24 h.
[0050] The TiO2@UiO-66 derivatization system was added to a 0.05 MCu(NO3)2·3H2O solution (solid-liquid ratio approximately 1 g:50 mL), and stirred at room temperature for 12 h to allow Cu to precipitate. 2+ Fully penetrate the UiO-66 MOF structure; The sample was then filtered and dried at 80°C to obtain TiO2@UiO-66 / Cu.
[0051] TiO2@UiO-66 / Cu was added to the EPDM system at 4 phr and mixed for 15 min at 80°C using a two-roll mill. Benzophenone (5 phr) was added and the mixture was continued for 10 min to avoid local agglomeration and migration. Finally, the uniformly mixed rubber compound was placed in a mold and hot-pressed and vulcanized in a flat vulcanizing machine at 175°C, 10 MPa, and 20 min. After cooling and demolding, the product was obtained.
[0052] Comparative Example 1: Preparation of Conventional EPDM Composite Materials EPDM rubber was selected as the matrix material, and carbon black N330 40 phr, naphthenic oil 10 phr, zinc oxide 5 phr, and stearic acid 1 phr were added in sequence. The mixture was kneaded for 8 minutes at 50°C using an open mill. Subsequently, 1.5 phr of sulfur, 1 phr of accelerator MBTS, and 0.5 phr of accelerator TMTD were added. Mix quickly at ≤50℃, continue mixing for 5 minutes, and let the compound stand at room temperature for 12 hours to eliminate internal stress.
[0053] The above-mentioned uniformly mixed rubber compound is placed directly into the mold and hot-pressed and vulcanized in a flat vulcanizing machine at 160℃, 10MPa and 30min. After cooling and demolding, the product is obtained.
[0054] Comparative Example 2: Composite material without UiO-66 (1) The EPDM matrix preparation process is the same as that of the raw materials and Example 1.
[0055] (2) Preparation of TiO2 / Cu composite filler: Tetrabutyl titanate was dissolved in anhydrous ethanol, and 5 vol% aqueous ethanol was added under stirring to hydrolyze it. Then, it was calcined in air at 550°C for 2 h to obtain TiO2 nanoparticles.
[0056] The obtained TiO2 was added to a 0.05MCu(NO3)2·3H2O solution at a solid-liquid ratio of 1g:50mL. After stirring at room temperature for 12h, the mixture was filtered and dried at 80℃ to obtain the TiO2 / Cu composite filler.
[0057] (3) Preparation of composite materials: TiO2 / Cu was added to the EPDM matrix at a rate of 4 phr, and the mixture was kneaded at 80°C for 15 min. Then add 5 phr of BP and continue mixing for 10 minutes; The compound was placed in a mold and vulcanized at 175°C and 10MPa for 20 minutes. After cooling, the sample was demolded to obtain the sample.
[0058] Comparative Example 3: Cu-free composite material (1) The EPDM matrix preparation and raw materials are the same as in Example 1.
[0059] (2) Preparation of TiO2@UiO-66: The preparation process of TiO2@UiO-66 is the same as that in Example 1, except that Cu(NO3)2 solution is not added after TiO2@UiO-66 is obtained.
[0060] (3) Preparation of composite materials: Add TiO2@UiO-66 to EPDM at a rate of 4 phr and mix. Add 5 phr of BP and continue mixing; The sample was obtained by vulcanization at 175℃ and 10MPa for 20 minutes.
[0061] Comparative Example 4: BP-free composite material (1) The EPDM matrix preparation is the same as that of the raw materials and Example 1.
[0062] (2) The preparation process of TiO2@UiO-66 / Cu is the same as that of the raw materials and Example 1.
[0063] (3) Preparation of composite materials: TiO2@UiO-66 / Cu was added to the EPDM matrix at a rate of 4 phr. Mix and knead at 80℃ for 15 minutes; Without adding BP, the sample was obtained by vulcanization at 175℃ and 10MPa for 20 minutes.
[0064] Performance Evaluation of Experiment Example 1 I. Experimental Objective The structural stability, active species generation, free radical generation ability, and self-healing mechanical properties of Example 1 and Comparative Examples 1-4 under γ-irradiation were evaluated.
[0065] II. Experimental Samples Experimental group: TiO2@UiO-66 / Cu / EPDM composite material prepared in Example 1.
[0066] Control group: EPDM composite materials prepared in comparative examples 1-4.
[0067] III. Irradiation Process Irradiation equipment: using 60 Co γ-ray source.
[0068] Sample preparation: Cut the vulcanized molded test pieces of Example 1 and Comparative Examples 1-4 into small pieces of 10mm×10mm×2mm, and dumbbell-shaped test pieces conforming to GB / T 528-2009 standard (gauge length 20mm, narrow section width 4mm).
[0069] Irradiation parameters: Absorbed dose: 50 kGy Dose rate: 10 Gy / min Irradiation temperature: room temperature (25±2℃) Irradiation atmosphere: air Irradiation procedure: The sample is placed on a rotating sample stage in the irradiation chamber to ensure uniform dose distribution. After irradiation, the sample is allowed to stand at room temperature for 24 hours to eliminate transient free radicals before subsequent characterization.
[0070] IV. Characterization of Structural Stability and Chemical State 1. X-ray diffraction (XRD) Sample preparation: The composite materials before and after irradiation were directly fixed on the sample stage using flat sheet samples for XRD analysis. The results showed that the material prepared in Example 1 still maintained the typical characteristic diffraction peaks of UiO-66 before irradiation, indicating that the framework structure of UiO-66 was not destroyed during the preparation process. However, after γ-irradiation, the overall peak intensity of the material prepared in Example 1 decreased slightly and showed slight broadening, indicating that the structure had some defects but did not completely collapse. At the same time, a weak new peak could be observed near 25°. Further confirmation of the formation of nanoscale TiO2 by subsequent transmission electron microscopy or X-ray photoelectron spectroscopy indicated that Ti underwent in-situ transformation.
[0071] In Comparative Example 2, due to the lack of the UiO-66 structure, the Ti precursor is prone to local aggregation during the preparation process. The TiO2 particles formed after irradiation are significantly larger in size, and the diffraction peaks are enhanced and narrowed, indicating that their dispersion uniformity is significantly reduced.
[0072] Although Comparative Example 3 contains UiO-66 and TiO2, the diffraction pattern changes little before and after irradiation due to the lack of Cu, indicating that the system lacks effective electronic control sites.
[0073] Comparative Example 4 lacks BP, and its structural changes are basically the same as those of Comparative Example 3.
[0074] Comparative Example 1 only showed a broad diffuse peak of the EPDM matrix, and no characteristic peaks related to the active components were observed after irradiation.
[0075] The above results demonstrate that UiO-66 can effectively regulate the formation location and dispersion state of TiO2, providing uniform active centers for subsequent free radical reactions.
[0076] 2. X-ray photoelectron spectroscopy (XPS) All samples before and after irradiation were cut into 5mm × 5mm pieces, fixed on conductive double-sided tape, and subjected to XPS analysis. Ultimately, the samples prepared in Example 1 were observed to exhibit XPS activity in Ti 2p. 3 / 2 The peak is located at approximately 458.5 eV, indicating that Ti mainly exists as T. i4+ It exists in form; while Cu 2p 3 / 2 A main peak appears at approximately 932-934 eV, accompanied by satellite peaks, indicating that Cu dominates the system. 2+ Mainly composed of Cu, with a possible small amount of Cu present. + This demonstrates the characteristic of reversible valence state changes, providing the possibility for electron transfer.
[0077] Although Ti was detected in Comparative Example 2, the change in Cu valence state was not obvious, indicating that the spatial distribution of Ti and Cu was uneven after the absence of UiO-66, resulting in a decrease in electron transfer efficiency.
[0078] Comparative Example 3, lacking Cu, only observed Ti. 4+ The signal cannot form an electron capture and transfer process.
[0079] The change in Cu valence state in Comparative Example 4 was significantly lower than that in Example 1, indicating that the electron utilization efficiency decreased after the absence of BP.
[0080] No Ti or Cu-related signals were detected in Comparative Example 1.
[0081] The results show that a stable and effective electron transport system can only be constructed when UiO-66, Cu and BP are present simultaneously.
[0082] 3. Scanning electron microscope (SEM) All samples before and after irradiation were cut into 3mm×3mm pieces, pasted onto an aluminum sample stage, and sputtered with gold (15mA, 60s) to enhance conductivity. The morphology and crack areas were then observed at magnifications of 500×, 2000×, 10000×, and 50000×.
[0083] In Example 1, after irradiation, the crack edges showed obvious passivation and bridging, and some microcracks tended to close.
[0084] In Comparative Example 1, the crack further expanded, and new secondary cracks appeared locally.
[0085] In Comparative Example 2, the crack edge remained sharp, with only a small amount of localized filling.
[0086] The crack width in Comparative Example 3 was significantly larger than that in Example 1, with only slight repair marks.
[0087] Comparative Example 4 shows that the crack basically retains its original morphology, and the repair phenomenon is weak.
[0088] 4. Transmission electron microscopy (TEM) and energy dispersive spectroscopy (EDS) All composite material samples before and after irradiation were ultrasonically dispersed in anhydrous ethanol, dropped onto a copper mesh (supported by a carbon film), dried at room temperature, and then the lattice fringes and pore structure were observed in HRTEM mode. The samples were then switched to STEM mode for EDS surface and spot scanning to analyze the distribution of elements such as Ti, Cu, Zr, C, and O.
[0089] The final results of Example 1 show that the material as a whole still exhibits a porous structure, and no obvious agglomeration of large particles was observed. Energy-dispersive X-ray spectroscopy revealed significant enrichment of Ti and Cu elements, indicating good dispersion of the active components within the material. Furthermore, comparing the samples before and after irradiation, a trend of gradually blurring and even local closure of the crack boundaries was observed in the crack region, indicating that the material possesses a certain degree of self-healing behavior.
[0090] In Comparative Example 2, obvious aggregation regions of Ti element were observed; Comparative Example 3 does not contain Cu. Although Comparative Example 4 contains Ti and Cu, the utilization efficiency of the active center is significantly reduced.
[0091] The results show that UiO-66 can improve the dispersibility of active components, Cu can promote electron migration, and BP can promote the generation of polymer free radicals. All three are indispensable.
[0092] V. Free Radical Generation Capacity Test (EPR) 1. Equipment and Parameters Equipment: Bruker EMXplus (X-band) Frequency: Approximately 9.8 GHz Magnetic field scanning range: 3000-4000G Modulation frequency: 100kHz Modulation amplitude: 1G Microwave power: 2.0mW Receiver gain: 3.0 × 10 4 Scan time: 60s Time constant: 20ms Total number of times: 4 2. Preparation of the trapping agent and sample Scavenger: 5,5-dimethyl-1-pyrrololine-N-oxide (DMPO, 98%, Sigma-Aldrich).
[0093] Operating steps: All samples (10 mg each) before and after irradiation were placed in centrifuge tubes. Add 1 mL of DMPO aqueous solution (100 mM, freshly prepared); Sonicate at room temperature in the dark for 5 minutes to ensure full contact. Quickly draw the mixture into a quartz capillary tube (1 mm inner diameter), and seal both ends; Place it into the EPR resonant cavity and immediately acquire the spectrum.
[0094] 3. Spectrum processing: Baseline correction, integration, and signal assignment were performed using Xenon software (referencing standard spectral libraries).
[0095] The irradiated sample can be classified as DMPO. - ·OH and DMPO - ·O2 -The characteristic signal of the unirradiated sample was weaker, indicating that γ-irradiation did indeed induce the generation of active free radicals. Specifically, Comparative Example 1 showed only a weak irradiation-induced free radical signal; Comparative Example 2 showed a significant decrease in free radical signal, approximately 60%-70% of that in Example 1; Comparative Example 3 showed a further decrease in free radical signal, only 40%-60% of that in Example 1; and Comparative Example 4, although some reactive oxygen species were detected, showed a significant reduction in the amount of polymer free radicals generated. Therefore, these results demonstrate that the material prepared according to this invention, while maintaining basic structural stability, can generate defects and in-situ active components under irradiation, thereby continuously generating free radicals and participating in reactions. This provides conditions for molecular chain reconstruction in the crack region, verifying the theoretical feasibility of the system achieving self-healing.
[0096] VI. Evaluation of Self-Healing Mechanical Properties 1. Preparation of dumbbell-shaped specimens Vulcanized molded sheets (thickness 2±0.2 mm) were prepared according to Example 1 and Comparative Examples 1-4. Use the GB / T 528-2009 standard cutting knife (dumbbell type, type 1) to punch out the specimens, with no less than 5 parallel specimens per group; Use a blade to pre-place a through-type microcrack (approximately 0.1-0.2 mm deep and 1 mm long) in the center of the narrow section of the sample, and record the initial state.
[0097] 2. Irradiation treatment Perform γ-irradiation under the conditions described in Part III (50 kGy, 10 Gy / min).
[0098] 3. Tensile test Equipment: Universal testing machine (Instron 5965, 500 N sensor) Fixture: Pneumatic flat-jaw clamp, pressure 0.4MPa, anti-slip rubber pad Gauge length: 20mm (marked with a marker pen) Tension rate: 50 mm·min -1 Environmental conditions: Temperature 23±2℃, relative humidity 50%±5% Operating steps: Use vernier calipers to measure the width and thickness of the narrow section of the sample; The sample is centered and clamped to avoid eccentricity; Initiate tensioning until fracture, and record the maximum force and elongation at break; Five parallel samples were tested for each condition, and the mean ± standard deviation was taken.
[0099] Calculate the tensile strength recovery rate and the elongation at break recovery rate; 4. Dynamic Mechanics Analysis (DMA) Equipment: TA Instruments Q800 Pattern: Stretching pattern, film / fiber clamp Sample size: 10mm × 5mm × 2mm Frequency: 1Hz Strain: 0.1% Heating rate: 3℃ / min Temperature range: –50℃ to 150℃ Operating steps: The sample is clamped at room temperature, and the force is reduced to zero. Cool liquid nitrogen to -50°C and hold at that temperature for 3 minutes; The energy storage modulus (E′), loss modulus (E″), and tanδ were continuously recorded at a temperature increase of 3℃ / min.
[0100] The final test results show that, compared with the material prepared in Comparative Example 1, the tensile strength and elongation at break of the sample prepared in Example 1 after irradiation show significant recovery. The tensile strength recovery rate can reach 80%-90%, which is about 30%-50% higher than the traditional repair system; the elongation at break recovery rate can reach 70%-90%, which is about 25%-45% higher. This indicates that effective structural reconstruction has occurred inside the material. Comparative Example 1 is only a conventional EPDM system, which mainly undergoes molecular chain breakage and oxidative degradation under γ-irradiation, with only a small amount of random free radical recombination. No obvious self-repair behavior was observed, and its tensile strength recovery rate was less than 10%, and its elongation at break recovery rate was less than 5%. Comparative Example 2 lacks UiO-66, Ti precursor and The subsequently formed TiO2 is difficult to achieve uniform dispersion, resulting in uneven distribution of active sites and local concentration of free radical generation areas. The tensile strength recovery rate drops to 55%-70%, and the elongation at break recovery rate drops to 45%-60%. In Comparative Example 3, due to the lack of Cu, the electron-hole pairs generated by TiO2 cannot be effectively separated, and a large number of charge carriers recombine. The ability to continuously generate reactive oxygen free radicals decreases, and the tensile strength recovery rate is 45%-60%, while the elongation at break recovery rate is 40%-55%. In Comparative Example 4, due to the lack of BP, although the system can generate some reactive oxygen free radicals, it is difficult to efficiently convert them into EPDM chain free radicals. The chain segment recombination efficiency in the crack region is significantly reduced, and the tensile strength recovery rate is only 35%-50%, while the elongation at break recovery rate is 30%-45%.
[0101] Next, the cracked area of the material prepared in Example 1 was observed using a scanning electron microscope. It could be seen that the crack edges gradually became blurred from being clear and sharp, and some areas showed closure or even bridging, indicating that the cracks were repaired at the microscale. At the same time, combined with dynamic mechanical analysis and testing, it could be observed that the storage modulus rebounded after irradiation, indicating that the structural integrity of the material was restored to a certain extent.
[0102] VII. Chemical Structure Evolution Analysis (FTIR) 1. Equipment and Parameters Equipment: Nicolet iS50 (Thermo Fisher) Attachment: Attenuated Total Internal Reflection (ATR, diamond crystal) Wavenumber range: 4000–400cm -1 Resolution: 4cm -1 Number of scans: 32 Detector: DTGS 2. Operating Procedures Background scan of the instrument (air, 32 times); All samples before and after irradiation were pressed directly onto the surface of the ATR crystal to ensure tight contact. Acquire single-beam spectra of all samples; After subtracting the ATR correction, the absorbance spectrum is obtained; Baseline correction, normalization, and characteristic peak assignment were performed using OMNIC software (C–O: ~1100 cm⁻¹). -1 C=O: ~1700-1730cm -1 C–H: ~2900cm -1 ).
[0103] The final results showed that no obvious new degradation peaks appeared in the polymer backbone-related characteristic peaks of the material prepared in Example 1. At the same time, some absorption peaks related to crosslinking or oxidation (such as CO and C=O) were slightly enhanced, indicating that more chain segment reconstruction or slight oxidation occurred in the system than large-scale fracture degradation.
[0104] In contrast, the pure EPDM material prepared in Comparative Example 1, after γ-irradiation, showed a 2900 cm⁻¹ temperature range. -1 The characteristic peaks of CH in the vicinity are significantly weakened, while those at 1700-1730 cm⁻¹ are significantly reduced. -1 The absorption peak of nearby C=O oxidation products was significantly enhanced, indicating that molecular chain breakage and oxidative degradation mainly occurred during irradiation. No characteristic changes that were obviously conducive to chain segment reconstruction were observed, indicating that the material basically does not have effective self-repair capabilities.
[0105] Comparative Example 2 also showed enhanced CO and C=O absorption peaks after irradiation, but the enhancement was significantly lower than that in Example 1. Additionally, strong oxidation characteristic peaks appeared in some regions. This indicates that the lack of the UiO-66 spatially confined structure makes it difficult for Ti species to achieve uniform dispersion, leading to local aggregation of active components, decreased free radical generation and utilization efficiency, and thus weakening the chain segment reconstruction process.
[0106] Comparative Example 3 showed only a weak enhancement of the CO characteristic peak after irradiation, while the C=O oxidation peak was relatively more pronounced. This indicates that the electron-hole pairs generated by TiO2 lack Cu. 2+ / Cu + In reversible systems, electron capture and transfer occur, but a large number of electrons are lost through recombination, which reduces the ability of free radicals to be continuously generated and thus reduces the efficiency of crosslinking and reconstruction.
[0107] In Comparative Example 4, although some oxidation product peaks could be detected, the enhancement of the CO absorption peak related to chain segment reconstruction was the least obvious. This indicates that although the system can generate some reactive oxygen species, due to the lack of BP activation of the EPDM molecular chain, the amount of polymer free radicals generated is insufficient, making it difficult to form an effective chain segment reconnection process.
[0108] The above experiments show that the material prepared in this application can continuously generate free radicals in the crack region and promote the reconnection of molecular chains under γ-irradiation, thereby achieving partial recovery of mechanical properties and improvement of structural integrity, demonstrating good self-healing potential.
[0109] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the protection scope of the technical solutions of the embodiments of the present invention.
Claims
1. An irradiated self-healing ethylene propylene rubber material, characterized in that, The irradiated self-healing ethylene propylene rubber material includes an ethylene propylene diene monomer (EPDM) rubber matrix, TiO2@UiO-66 / Cu dispersed in the EPDM rubber matrix, and benzophenone. In the TiO2@UiO-66 / Cu structure, TiO2 is formed by in-situ hydrolysis of tetrabutyl titanate and dispersed in the porous structure of the UiO-66 metal-organic framework, while Cu is expressed as Cu 2+ The form is loaded in the UiO-66; Based on 100 phr EPDM rubber, the amount of TiO2@UiO-66 / Cu added is 1-5 phr, and the content of benzophenone is 3-8 phr.
2. The irradiated self-healing ethylene propylene rubber material according to claim 1, characterized in that, The EPDM rubber matrix, based on 100 phr EPDM rubber, comprises 40-45 phr rubber carbon black, 10-20 phr paraffin oil, 5-10 phr zinc oxide, 1-3 phr stearic acid, and 1-2 phr dicumyl peroxide.
3. A method for preparing an irradiated self-healing ethylene propylene rubber material as described in any one of claims 1-2, characterized in that, Includes the following steps: Tetrabutyl titanate was dissolved in anhydrous ethanol and added dropwise to a dispersion of UiO-66. It was hydrolyzed to form TiO2@UiO-66. After treatment with Cu(NO3)2 solution, TiO2@UiO-66 / Cu was obtained. The EPDM rubber matrix, TiO2@UiO-66 / Cu and benzophenone are mixed, compounded and vulcanized.
4. The preparation method according to claim 3, characterized in that, The reaction to form TiO2@UiO-66 by hydrolysis is initiated by adding 1-5 vol% aqueous ethanol as a trigger, followed by calcination at 450-550℃ for 2-4 hours.
5. The preparation method according to claim 3, characterized in that, The concentration of the Cu(NO3)2 solution was 0.01-0.1M, and the treatment time was 6-12h.
6. The preparation method according to claim 3, characterized in that, The solid-liquid ratio of the TiO2@UiO-66 to the Cu(NO3)2 solution is 1g:50mL.
7. The preparation method according to claim 3, characterized in that, The mixing is carried out at 60-80℃, the vulcanization temperature is 165-175℃, the vulcanization pressure is 8-12MPa, and the vulcanization time is 10-20min.
8. The application of an irradiated self-healing ethylene propylene rubber material as described in any one of claims 1-2 as a cable insulation or sealing material in a nuclear radiation environment.
Citation Information
Patent Citations
Self-repairing epoxy resin composition, self-repairing epoxy resin composite material as well as preparation method and application of self-repairing epoxy resin composite material
CN118063933A
Polymer composite material coordinated by multi-element liquid metal alloy as well as preparation method and application of polymer composite material
CN121005961A